2012
DOI: 10.1136/bjophthalmol-2011-300996
|View full text |Cite
|
Sign up to set email alerts
|

Use of iris recognition camera technology for the quantification of corneal opacification in mucopolysaccharidoses

Abstract: Mucopolysaccharidoses (MPS) can cause corneal opacification that is currently difficult to objectively quantify. With newer treatments for MPS comes an increased need for a more objective, valid and reliable index of disease severity for clinical and research use. Clinical evaluation by slit lamp is very subjective and techniques based on colour photography are difficult to standardise. In this article the authors present evidence for the utility of dedicated image analysis algorithms applied to images obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 5 publications
(4 reference statements)
0
25
0
Order By: Relevance
“…The COM scores, however, also may be influenced by other corneal disease states. 8 This can be seen in patient 6 whose left eye had an increase in COM score due to worsening of corneal clouding due to secondary glaucoma requiring subsequent surgery. The left eye was excluded from COM score analyses as her large peripheral iridotomy meant the image was no longer standardized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The COM scores, however, also may be influenced by other corneal disease states. 8 This can be seen in patient 6 whose left eye had an increase in COM score due to worsening of corneal clouding due to secondary glaucoma requiring subsequent surgery. The left eye was excluded from COM score analyses as her large peripheral iridotomy meant the image was no longer standardized.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that new methods to quantify corneal clouding 8,13 are of use in monitoring changes over time and effect of treatment. The technique of iris camera assessment of corneal clouding also may be applicable to other corneal pathologies resulting in opacification, such as corneal dystrophy, bullous keratopathy, and infective keratitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Communicating hydrocephalus. Hearing loss [2], corneal opacities [54,55]. Hepatosplenomegaly, umbilical and inguinal hernias [39,40].…”
Section: Othersmentioning
confidence: 99%